2017
DOI: 10.1093/mmy/myw136
|View full text |Cite
|
Sign up to set email alerts
|

Bone and joint infections caused by mucormycetes: A challenging osteoarticular mycosis of the twenty-first century

Abstract: Osteomyelitis and arthritis caused by mucormycetes are rare diseases that rank among the most challenging complications in orthopedic and trauma surgery. The aim of this work is to review the epidemiological, clinical, diagnostic, and therapeutic aspects of the osteoarticular mucormycosis with particular emphasis on high-risk patients. A systematic review of osteoarticular mucormycosis was performed using PUBMED and EMBASE databases from 1978 to 2014. Among 34 patients with median age 41 (0.5-73 years), 24 (71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 55 publications
1
26
0
1
Order By: Relevance
“…Zakażenie najczęściej następowało przez bezpośrednie wprowadzenie patogenu, a także rozsiew drogą krwionośną. Wśród czynników etiologicznych dominowały rodzaje Rhizopus i Apophysomyces [45].…”
Section: Zakażenia Kości I Stawów (Bj)unclassified
“…Zakażenie najczęściej następowało przez bezpośrednie wprowadzenie patogenu, a także rozsiew drogą krwionośną. Wśród czynników etiologicznych dominowały rodzaje Rhizopus i Apophysomyces [45].…”
Section: Zakażenia Kości I Stawów (Bj)unclassified
“…Diagnosis of this rare manifestation is challenging in a setting with high burden of tuberculosis, like ours. Biopsy is the mainstay of diagnosis as imaging features are non-specific (4).…”
Section: Casementioning
confidence: 99%
“…Osteoarticular mucormycosis (excluding extension following rhinosinusitis) is a rare manifestation of this disease. In a systematic review, 34 reported cases were identified between 1978 and 2014 (4). We reported a case of long bone mucormycosis and Mycobacterium abscessus infection recently (5).…”
Section: Introductionmentioning
confidence: 99%
“…That review reported a mortality rate of 24% for patients with osteoarticular mucormycosis. However, accurate early diagnosis and long-course therapy with a combined medical-surgical approach may result in favorable outcomes (1). Recent guidelines proposed a multimodal approach for management of posttraumatic Mucorales bone and joint infections, including surgical debridement (to clear margins) (12) and long-term antifungal treatment using Here we report the first successful conservative orthopedic treatment of Saksenaea sp.…”
mentioning
confidence: 95%
“…M ucorales osteomyelitis still presents diagnostic and therapeutic challenges and is associated with high mortality rates despite a combined therapeutic strategy involving antifungal treatment and surgery (1). Members of the order Mucorales are present in soil and plant debris and could be responsible for osteoarticular mucormycosis as a consequence of contamination through disrupted cutaneous barriers after traumatic injury (2).…”
mentioning
confidence: 99%